Pembelajaran yang Repetitif Meningkatkan Keluhan Musculoskeletal dan Stres Akibat Belajar serta Menurunkan Motivasi Siswa di SMA Negeri 10 Denpasar - I Made Heri Gunawan (Jurnal Pendidikan Biologi Undiksha, 2024)
This study aims to determine the application of repetitive learning increases musculoskeletal complaints and stress due to learning and decreases learning motivation. This type of research is a quasi-experimental study with a nonequivalent randomized pre and post test control group design. The dependent variables of this study include: (1) musculoskeletal complaints were recorded using the Nordic Body Map questionnaire, (2) stress due to learning was recorded using the stress questionnaire due to learning, (3) learning motivation was recorded using the learning motivation questionnaire. Data were analyzed using an independent sample t-test with a significance level of 5%. The results of this study indicate that (1) repetitive learning significantly increases musculoskeletal complaints in students by 27.95%, (2) repetitive learning significantly increases stress due to learning by 13.79%, (3) repetitive learning significantly decreases learning motivation by 3.36%.